Faktor-faktor Yang Mempengaruhi Keputusan Pembeliaan Di Diva Swalayan Kraksaan Kabupaten Probolinggo - Widiantika, Dedi; Haris, R Abdul; Amani, Tatik (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at Diva Swalayan Kraksaan, Probolinggo Regency with the aim to determine the effect of product quality, service quality and price on purchasing decisions at Diva Swalayan Kraksaan, Probolinggo Regency partially. The type of research used is quantitative research with descriptive statistical analysis. The population is all visitors to Diva Swalayan Kraksaan, Probolinggo Regency with a sample of 98 people, and the sampling method is probability sampling. In proving and analyzing this, validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination and hypothesis testing are used. The results showed that there was a significant influence partially and simultaneously between product quality, service quality, and price on purchasing decisions at Diva Swalayan Kraksaan, Probolinggo Regency. The product quality variable has a greater (dominant) influence on purchasing decisions at Diva Swalayan Kraksaan, Probolinggo Regency